2023
DOI: 10.1017/s1743923x23000156
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the “Hidden Curriculum” in Political Science Publishing

Abstract: Across the academy, there is growing concern over diversity within academic institutions. According to recent research published in three top political science journals, members of historically marginalized groups remain underrepresented and marginalized in submissions, publications, and even reviewer pools (Ayoub 2022; Bell et al. 2020; Reinhardt, Windsor, and King 2022). Expectations that scholars, especially early career researchers (ECRs), “publish or perish” thus exacerbate intersectional inequalities wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We believe that as the official journal of the Women, Gender, and Politics Section of the American Political Science Association, the content of Politics & Gender should reflect the diversity of authors, methods, and topics found across the broader gender and politics research community. However, not all authors have the full information on how to best prepare their manuscripts-or, indeed, what to expect during different parts of the review process (see Anlar and Phillips 2023).…”
mentioning
confidence: 99%
“…We believe that as the official journal of the Women, Gender, and Politics Section of the American Political Science Association, the content of Politics & Gender should reflect the diversity of authors, methods, and topics found across the broader gender and politics research community. However, not all authors have the full information on how to best prepare their manuscripts-or, indeed, what to expect during different parts of the review process (see Anlar and Phillips 2023).…”
mentioning
confidence: 99%